Child restraint systems: Understanding confidence in proper use and addressing the need for education - Jennifer Britton; Kaitlyn Jacobs; Tania Haidar; Christopher Stolworthy; Alison Armstrong; Neil Merritt; Neil Parry; Kelly Vogt; Fran Priestap (Heliyon, 2023)
Objective: To quantify the extent of proper local child restraint system (CRS) use and to better understand changes to the level of self-reported confidence with increased CRS installations. With the goal being to improve safety for children travelling in personal vehicles across London, ON and the region. Methods: Public CRS clinics were initiated by Injury Prevention staff after they obtained the Child Passenger Safety Technician certification. Additionally, an online survey was commissioned targeting Ontario parents who had installed at least one CRS in the last five years. Results: From September 2018 to September 2019, 96 comprehensive CRS checks were performed, with 29% of systems found to be installed correctly. Survey results showed a high level of reported confidence with CRS installation (N = 514, 70% female, 43% one child). Parents who had installed only one CRS reported higher confidence in their first install, compared to parents who had installed two or more systems. Conclusions: The error rate with CRS installation and use seen in London, Ontario and the region, is similar to that reported in previous research. Survey results showed high levels of self-reported confidence in CRS use, especially for parents who have installed only one CRS. There presents a need to better understand the root cause of the discrepancy between level of confidence and proper CRS use and to expand our understanding of CRS knowledge retention and transferability to subsequent systems.